Efficacy, safety and acceptability of a new chewable formulation versus the solid tablet of mebendazole against hookworm infections in children: An open-label, randomized controlled trial - Palmeirim, Marta S. (EClinicalMedicine, 2020)
BACKGROUND: Soil-transmitted helminths (STHs) infect almost 1·5 billion people worldwide. The control of STH infections is based on preventive chemotherapy using either albendazole or mebendazole. Before being widely used, a sufficient body of evidence on efficacy, safety and acceptability is warranted for the new chewable child-friendly formulation of mebendazole that was recently developed. METHODS: We conducted a randomised controlled superiority trial in four primary schools and kindergartens on Pemba Island, Tanzania. We considered eligible children aged 3 to 12 years with a hookworm infection intensity of at least 50 eggs per gram (EPG) of stool and no chronic diseases. Participants were allocated to treatment arms (ratio 1:1) using a computer generated random sequence. Our primary outcome was geometric mean based egg reduction rate (ERR) against hookworm assessed 14–21 days post-treatment. This trial complete and is registered with ClinicalTrials.gov, number NCT03995680 (June 24, 2019). FINDINGS: 397 children were eligible and randomised into the solid (198) or chewable (199) tablet arms, of whom 393 were analysed. We found no significant difference between both formulations in terms of ERR (solid 70·8% versus chewable 68·5%, difference in ERR(geometric mean) 2·3%-points, 95% CI -7·8 to 12·6, p = 0.65) and CR (11·2 versus 12·7%, 95% CI -4·9 to 7·9, p = 0.65) against hookworm infections. Adverse events were mild in both treatment arms. INTERPRETATIONS: Though we could not demonstrate superiority in terms of efficacy of the new formulation, the difference between arms was small and therefore, the chewable formulation could be safely used as an alternative to swallowable tablets, in particular in young children who may have swallowing difficulties. This might help increase compliance and, consequently, enhance the effect of preventive chemotherapy.